New evidences about the burial practices in urns in "Los Colorados", La Rioja province, Argentina - Lanzelotti, Sonia L.; Acuña Suarez, Gabriel E.; Aranda, Claudia M.; Luna, Leandro H. (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
The results of the research carried out on an urn burial found in the town of Los Colorados, La Rioja province, Argentina, are presented. The fieldwork and laboratory analysis offered information about the formation processes and allowed the identification of the use of beaten clay as a burial practice to cover the urn and the placement of a base of rocks inside the vessel, as well as the removal of the edge. The recovered human remains correspond to an individual between 1 and 2 years of age-at-death, associated with numerous shell beads, that probably belonged to a necklace, as grave goods. A radiocarbon dating was carried out on the human remains (440±34 years BP), which is consistent with the stylistic and formal characteristics of the vessel and with the last recorded stage in the associated rock art, corresponding to the Regional Developments or local Late period. It is emphasized that the excavation and analysis of the recovered sample were very valuable not only for the academic community, but also for the local population.